The difficulties in learning music theory among music students in UiTM / Aeryna Fareez Khasri - Khasri, Aeryna Fareez (Faculty of Music, 2016)
This study discusses the difficulties in learning music theory among music students in UiTM. The objectives of this study are to identify the topic of music theory that students are weak in, to find out factors that music students are weak in learning music theory and to identify which method that could enhance their understanding of music theory. The method of instruments used for this study is interview which is in qualitative method. There are 6 students (2 males, 4 females) was selected to involved in these interviews. All the students was from Bachelor Degree in Music Education UiTM Shah Alam from semester 2,3 and 4. The interview consist of 3 section which was the first section require the respondent to answer the simple test of Music theory question. The purpose of the test was to observe student's current knowledge of simple music theory questions. The result shows that none of the respondent are able to answer all question correctly. The data gathered from the interviewed able to prove that students are indeed are having difficulties in learning music theory inside and outside class sessions.